The contribution of schooling to learning gains of pupils in Years 1 to 6. Issue 3 (3rd July 2017) - Luyten, Hans; Merrell, Christine; Tymms, Peter
ABSTRACT: By means of a regression-discontinuity approach with multiple cut-off points, the effects of age and schooling on learning gains in English primary schools are estimated. The analyses relate to over 3, 500 pupils in 20, predominantly independently funded, schools and focus on 4 different learning outcomes. In order to take into account delayed and accelerated school careers, an intention-to-treat analysis was applied. The findings reveal substantial effects of schooling, which in line with previous studies in English primary education account for about 40% of the total learning gains. The year-to-year gains show a declining trend as the school career progresses. The analyses produce evidence for both decreasing effects of schooling on achievement and a weakening age‒achievement relationship in the higher years of primary education.